Effective Elimination of Structural Racism - Guerrero, Erick (IntechOpen, 2022)
The increasing recognition of the role of structural racism affecting vulnerable groups motivated the scholarly work presented in this volume. The authors' rigorous scholarship seeks to help readers identify and understand how structural racism impacts vulnerable groups and how effective practices may dismantle these structural forces. Nine chapters provide unique, comprehensive, and science-based approaches to identify and eliminate structural racism within healthcare, politics, and education systems. Policymakers, system administrators, scholars, students, and the public will benefit from the authors' critical examples of structural racism within public systems across different countries, as well as from their proposed solutions.